2016
DOI: 10.1139/cjc-2015-0426
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquity of ClNO2 in the urban boundary layer of Calgary, Alberta, Canada

Abstract: The role of nitryl chloride (ClNO2) as a nocturnal nitrogen oxide reservoir species and chlorine atom precursor is well established for polluted coastal areas, but its role at midcontinental locations is less clear. In this paper, intermittent measurements over the course of several seasons of ClNO2 mixing ratios by iodide ion chemical ionization mass spectrometry in Calgary, Alberta, Canada, are presented. Mixing ratios were highly variable between nights and seasons and depended on the abundances of precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(81 citation statements)
references
References 80 publications
10
69
2
Order By: Relevance
“…8a, right-hand axis), of which 600 pptv was produced before midnight. The amount of ClNO 2 produced relative to this amount, φ'(ClNO 2 ), was very small (median 0.17 %, maximum 5.4 % on the morning of 2 August) and considerably less than reported by our group for Calgary (median 1.0 %) (Mielke et al, 2016) and Pasadena, CA (median 12 %) (Mielke et al, 2013).…”
Section: Metrics Of Nocturnal Nitrogen Oxide Chemistrycontrasting
confidence: 62%
See 1 more Smart Citation
“…8a, right-hand axis), of which 600 pptv was produced before midnight. The amount of ClNO 2 produced relative to this amount, φ'(ClNO 2 ), was very small (median 0.17 %, maximum 5.4 % on the morning of 2 August) and considerably less than reported by our group for Calgary (median 1.0 %) (Mielke et al, 2016) and Pasadena, CA (median 12 %) (Mielke et al, 2013).…”
Section: Metrics Of Nocturnal Nitrogen Oxide Chemistrycontrasting
confidence: 62%
“…Figure 10 shows the instantaneous radical production rates of Cl and OH, P (Cl) = j (ClNO 2 ) × [ClNO 2 ] and P (OH) from reaction of O( 1 D)+H 2 O. The latter was calculated from an assumed steady state in O( 1 D) with respect to its production from O 3 photolysis and reactions with N 2 , O 2 , and H 2 O as described by Mielke et al (2016). This analysis does not account for OH radical production from photolysis of nitrous acid or aldehydes and, hence, overestimates the importance of Cl radicals.…”
Section: Impacts Of Clno 2 On Radical Productionmentioning
confidence: 99%
“…Elevated ClNO 2 mixing ratios were firstly observed in several polluted coast regions (for instance, the coasts of Texas and California, and the Los Angeles Basin), resulting from the strong emission of NO x and abundant chloride from sea salt aerosols (Osthoff et al, 2008;Mielke et al, 2013;Tham et al, 2014). Recently, significant ClNO 2 production was also observed in some inland areas (such as Colorado, Hessen, and Alberta), with a mixing ratio of up to several hundreds of pptv or even exceeding 1.0 ppbv (e.g., Thornton et al, 2010;Mielke et al, 2011Mielke et al, , 2016Phillips et al, 2012;Riedel et al, 2013;Faxon et al, 2015). Anthropogenic sources of chlorine including coal combustion in power plants, industries, and biomass burning may potentially facilitate ClNO 2 production .…”
Section: Introductionmentioning
confidence: 99%
“…20 Recent work has shown that chlorine atoms oxidize volatile organic compounds (VOCs) and produce ozone more efficiently than hydroxyl radicals, even in small quantities. 2,21,[25][26][27][28] Production of chlorine atoms results from photolysis and oxidation reactions of precursor molecules. 23 Both scenarios have significant air quality and environmental implications; thus, monitoring of chlorine atoms is essential.…”
Section: Introductionmentioning
confidence: 99%